Influence of Tool-Pin Profile on Properties of Friction Stir Processed AA 2014 Under Natural and Flood Cooling - Dhaliwal, Gagandeep Singh; Kumar, Pardeep (Asian Review of Mechanical Engineering, 2014)
Aluminium alloys, possessing good strength to weight ratio, are extensively employed in various fields of technology. Friction stir processing (FSP) is an allied process of friction stir welding (FSW) that is used to transform the material properties. FSP performed on surface can transform the surface properties of certain material and can also transform the mechanical properties, if carried out in bulk of material. Investigations havebeen carried out by number of researchers to see the influence of FSP parameters and the simultaneous cooling on different properties of different materials. In the present research work, the work was carried out to see the influence of tool-pin profile on the properties of aluminium alloy AA2014, under natural and flood cooling conditions. AA2014 is commonly used in aerospace industry and in defence equipment. AA2014 was friction stir processed with three types of tool-pin profiles and freezing the other process parameters of FSP, on the basis of literature. The processed specimens were characterized with X-ray radiography and microstructure analysis. Micro-hardness and the tensile strength of the processed specimens were also tested. Among the processed specimens, the highest hardness was obtained with square tool-pin profile under flood cooling conditions. The refinement in microstructure has been observed to be the reason of the same.